The interactive influence of gender and ergonomic factors, alongside psychosocial associations, on work-related musculoskeletal disorders in Saudi dental students: a cross-sectional study - Kassim, Saba; Alblehshi, Hawazin Mohammad; Bakeer, Hala; Almeida, Manuel Barbosa; Al-Harkan, Doaa S.; Jambi, Safa; Felemban, Doaa; Alaajam, Wafa; Althagafi, Nebras; Fadel, Hani T.; Alsharif, Alla (PeerJ, 2025)
Background Work-related musculoskeletal disorders (WMSDs) among dental students have been documented, with female gender frequently identified as a contributing factor. Yet there is a lack of studies that have investigated the underlying factors between gender and WMSDs. Objectives The primary aim of this study was to examine the interaction of gender with two specific ergonomic risk factors—academic level and weekly training hours—on WMSDs. Additionally, the associations of psychosocial factors, namely perceived stress and social support, with WMSDs were explored separately. Methodology A self-reported questionnaire was distributed among a convenience sample of 409 undergraduate dental students at a dental school in Western Saudi Arabia. The questionnaire comprised socio-demographic characteristics, WMSDs using validated questionnaire (Nordic Musculoskeletal Questionnaire), the Perceived Stress Scale, and the Perceived Social Support Scale. Descriptive, bivariate and logistic regression analyses were performed. Results The median/interquartile range age of the participants was 21 (2) years, and 59% were males. Of the participants, 71% (95% confidence interval (CI) [64.3–76.7]) self-reported WMSDs in at least one area of body over the past 12 months, with the most reported WMSDs being in the lower back, followed by the neck, wrists/hands, and shoulders at 48%, 45%, 31% and 30%, respectively. In fully adjusted logistic regression, being a female and the synergy between gender (female), academic levels and assigned training hours per week were significantly associated with self-reported WMSDs (adjusted odd ratio (AOR): 0.05, 95% CI [0.02–0.17], p < .001; AOR: 1.33, 95% CI [1.07–1.65], p = .011). Conclusion In this study sample, psychosocial factors were not associated with WMSDs. However, the results suggest that female student were more likely to self-report WMSDs than counterparts. Notably, the interaction between gender, academic level and number of hours training assigned per week contributed significantly and positively in self-reported WMSDs specifically among female students. Intervention may consider female students at higher academic levels with training demands.
Keywords: Ergonomics; Musculoskeletal pain; Occupational dentistry; Psychosocial factors; Saudi Arabia; Gender; Dental students